2018
DOI: 10.1016/j.jaci.2017.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar eosinophilia in current smokers with chronic obstructive pulmonary disease in the SPIROMICS cohort

Abstract: SUMMARY Active smoking in stable COPD subjects significantly increased eosinophil accumulation in the distal airspaces, but not in sputum or peripheral blood. Our findings support the need to investigate this cell-type as a potential driver of COPD symptomatology and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…For this subgroup, the levels of CRP, NLR and ESR were significantly lower, suggesting that an eosinophilic phenotype could be defined, as previous reports stated [29]. The blood EOS levels were significantly lower in active smokers versus non-smokers or former smokers, suggesting that smoking might increase the recruitment or retention of eosinophils in specific sites, perhaps in distal lung areas [30], as recently reported by Martinez et al (2018). Only for the active smokers group of our study, the patients with higher EOS levels had a greater BODE index, indicating a connection between these two parameters, both proposed as biomarkers of survival and mortality.…”
Section: Discussionsupporting
confidence: 67%
“…For this subgroup, the levels of CRP, NLR and ESR were significantly lower, suggesting that an eosinophilic phenotype could be defined, as previous reports stated [29]. The blood EOS levels were significantly lower in active smokers versus non-smokers or former smokers, suggesting that smoking might increase the recruitment or retention of eosinophils in specific sites, perhaps in distal lung areas [30], as recently reported by Martinez et al (2018). Only for the active smokers group of our study, the patients with higher EOS levels had a greater BODE index, indicating a connection between these two parameters, both proposed as biomarkers of survival and mortality.…”
Section: Discussionsupporting
confidence: 67%
“… 68 Furthermore, the subset of patients who underwent bronchoscopy in the Subpopulations And Intermediate Outcomes in COPD Study (SPIROMICS; NCT01969344) 69 showed significantly increased BAL eosinophils for current smokers with COPD compared with former smokers with and without COPD, as well as current smokers without COPD. 70 Other large observational studies – Genetic Epidemiology of COPD (COPDGene; NCT00608764) 71 and The Novel Observational Longitudinal Study (NOVELTY; NCT02760329) 72 – that are currently under way will further characterize patients with COPD and healthy volunteers and provide more insight into the eosinophil profiles of these populations.…”
Section: Eosinophils: Characteristics and Methods Of Quantificationmentioning
confidence: 99%
“…BAL fluid eosinophil counts were significantly increased in current smokers with COPD relative to those in former smokers with or without COPD, current smokers without airflow obstruction, or never smokers, whereas there was no difference between eosinophil percentages in peripheral blood and sputum. 105 Moreover, BAL fluid eosinophil counts did not correlate significantly in any sample type with FEV 1 percent predicted or imaging variables (percentage emphysema or Pi10). BAL fluid eosinophil counts showed no correlation with blood or sputum eosinophil counts.…”
Section: Biologics In Asthmatic Patientsmentioning
confidence: 74%